(untitled) (Journal Of Educational and Psychological Researches, 2015)
The current study aimed at identifying the impact of each of the full and part time summer enrichment programs on the performance of gifted students. Moreover, it aimed to study the difference between the full and part time programs on the performance of gifted students. The study sample consisted of (115) students from the full time programs and (137) students from the part time programs, they have been randomly selected from the gifted students participating in the full and part time summer enrichment programs. The researcher used the scale of student performance. The results indicated that there were statistically significant differences between the averages of the pre and post applications of the students participating in the full time programs on the dimensions of (scientific knowledge, research skills, creative thinking, problem-solving skills, critical thinking, leadership, motivation, and independence) and the total score on the scale of student performance. Furthermore, the results showed a statistically significant difference between the averages of the pre and post applications of the students participating in the part time programs in the dimensions of (scientific knowledge, research skills, critical thinking skills, creative thinking, problem-solving skills, leadership, and independence) and the total score on the scale of student performance. Whereas, the results revealed that there were no statistically significant differences between the averages of the pre and post applications of the students participating in the part time programs on the dimension of motivation. The results also indicated that there were statistically significant differences between the mean scores of students of the full and part time programs on the dimensions of (scientific knowledge, scientific research skills, creative thinking, leadership, motivation, and independence) and the total score on the scale of student performance in favor of the full time programs. While the results showed that there were no statistically significant differences between the mean scores of students in the full and part time programs on the dimensions of (critical thinking, and problem solving). Results were discussed in light of the research literature, and some recommendations related to the results of the research topic were presented.